Financial literacy and IPO underpricing - JIA, Xiaoran (Institutional Knowledge at Singapore Management University, 2024)
Using an international sample of IPO firms and two country-level measures of financial literacy, we find strong evidence that financial literacy is negatively associated with IPO underpricing. In cross-sectional analyses, we find that the effect of financial literacy in reducing IPO underpricing is more pronounced when the information environment is less transparent. Employing path analysis, we document that information friction, firm transparency, and stock market participation are mechanisms that mediate this relationship. Our study contributes to and extends the literature by providing strong evidence that citizens' financial literacy has an important and consistent influence on IPO underpricing.